Multi Agents Systems and Green Supply Chain: A Literature Review - Idrissi, Mohamed Dif El; Charkaoui, Abdelkabir; Echchatbi, Abdelwahed (Research Highlights in Science and Technology Vol. 2, 2023)
The present review summarizes the main ideas, precises the contributions and provide a recommendation for future researches regarding multi agents systems and Green Supply Chain management. Green supply chain issues have attracted a lot of attention in recent years with growing awareness of environmental concerns. This has drawn the considerable world-wide attention of academics and practitioners. However, coordination and collaboration among all stakeholders are challenging during implementation. As a result, numerous GSCM models and frameworks, including multi agent systems (MAS), are suggested to lessen the complexity of the supply chain. Recycling of used products and the related logistics management pose a significant challenge to manufacturing industries. The adopted research methodology is to build a literature review to bring knowledge on this topic based on already existing literature. The proposed work may offer an effective methodological foundation for resolving the GSCM modelling and collaboration problem using a multi-agent strategy. One angle for future research is the suggestion of additional frameworks based on the multi-agent approach.